Perception of Women towards Indian Stock Market with Reference to Demographic Factors - Dr. Sanjeet Kumar; Prashant Kumar (Researchers World - International Refereed Social Sciences Journal, 2021)
The participation of women in the economy is important in order to enhance and contribute towards raising the economic potential of a country. Women invest in stock market because of high return, high liquidity, income stability and variety of benefits associated with stock market. As investment decision of women depends upon number of behavioral aspects like their understanding, perception, attitude and preferences which form their behavior. On the basis of these behavioral elements, women arrive at a conclusive decision such as whether to invest or not in a particular investment avenue. The basic factors that form the rational behavior of investors are investor’s personal characteristics such as age, occupation, investments experience and income level of investors. The present study aims to identify the perception of women investors towards investment in Indian stock market with regard to demographic factors. A random sample of 400 women investors were selected from Haryana, India. To analyze the data, ANOVA were applied to investigate the difference between demographic factors and perception of women. The present research will assist not only the women investors but also the different financial institutions, investment consultants, stock broking houses and other participants of stock market in exploring the factors that influence the perception of women about stock market